Analysis of cervical tracheal characteristics of obstructive sleep apnoea-hypopnoea syndrome patients using ultrasound - Lun, Haimei; Wei, Lisi; Ye, Linsong; Wei, Liu; Li, Xiaoxi; Zhong, Weixian; Zheng, Hongyu; Hu, Qiao (Frontiers in Medicine, 2025)
ImportanceCervical tracheal characteristics in OSAHS patients remain unclear.ObjectiveThis study aimed to analysis the cervical tracheal characteristics of obstructive sleep apnoea-hypopnoea syndrome (OSAHS) patients using ultrasound.MethodsOne hundred and thirteen patients with OSAHS and 113 age-, sex-, height-, weight-, and BMI-matched healthy controls underwent cervical tracheal sonographic examination. Tracheal wall motion was monitored and sonographic measurements of the airway lumen were obtained during quiet respiration, deep respiration, and the Müller maneuver. Tracheal displacement during the Müller maneuver was monitored and quantified. Measurements were compared between groups.ResultsAdequate visualization of cervical tracheal dimensional changes during the Müller maneuver was obtained in 91.15% of patients with OSAHS and 99.12% of healthy subjects. The cervical trachea had the smallest lateral diameter during the Müller maneuver (P < 0.001) in patients with OSAHS and healthy controls. The cervical trachea moved caudally during the Müller maneuver, and its peak tracheal displacement was greater in patients with OSAHS than that in the healthy controls (P < 0.001). There was a positive relationship between peak tracheal displacement during the Müller maneuver and apnoea-hypopnoea index (AHI; P < 0.001).ConclusionOSAHS patients have greater caudal tracheal displacement and greater tracheal size than healthy controls. Ultrasonography may be especially suited for precisely evaluating the trachea and can provide a reference for the airway assessment and management of OSAHS.